Superconducting fluctuation effect in CaFe0.88Co0.12AsF. (13th September 2016) - Xiao, H; Gao, B; Ma, Y H; Li, X J; Mu, G; Hu, T
Abstract: Out-of-plane angular dependent torque measurements were performed on CaFe0.88 Co0.12 AsF single crystals. Superconducting fluctuations, featured by magnetic field enhanced and exponential temperature dependent diamagnetism, are observed above the superconducting transition temperature T c, which is similar to that of cuprate superconductors, but less pronounced. In addition, the ratio of T c versus superfluid density follows well the Uemura line of high- T c cuprates, which suggests the exotic nature of the superconductivity in CaFe0.88 Co0.12 AsF.